The Influence of Training, Competence, and Work Motivation on the Performance of Yonzikon 14/SWS Soldiers - Achmad Afandi; Asep Kurniawan (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2024)
Yonzikon 14/SWS is a military technical unit responsible for providing support in the area of permanent construction. It is of the utmost importance for this unit to maintain a high level of operational readiness and meet demanding duties in a prompt and efficient manner. However, the issue at Yonzikon 14/SWS lies in the subpar performance of troops in providing assistance to engineer combat operations, which is a cause for concern in terms of human resources. The objective of this study is to ascertain the description and impact of training, competency, and job motivation on performance. This research methodology employs quantitative techniques and utilizes descriptive analysis. The study utilized a sample size of 91 respondents, selected by the basic random sampling technique. The results of the descriptive analysis indicate that the levels of training, competence, work motivation, and performance are classified as extremely high. The findings of the study indicate that training, competence, and work motivation exert a partial or simultaneous impact on performance.